Diagnosis and treatment of polycythemia vera: Brazilian experience from a single institution - Linardi, Camila da Cruz Gouveia; Pracchia, Luís Fernando; Buccheri, Valeria (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: Polycythemia vera (PV) is a chronic myeloproliferative disorder characterized by predominant proliferation of erythroid precursors. Few data are available concerning Brazilian patients with this condition. The aim of this study was to describe clinical and demographic characteristics of PV patients at diagnosis and analyze their long-term outcomes. DESIGN AND SETTING: Retrospective study at the Division of Hematology, Faculdade de Medicina da Universidade de São Paulo (FMUSP), São Paulo. METHODS: All consecutive patients with PV diagnosed according to World Health Organization criteria were eligible for this study. Clinical and demographic characteristics, thrombotic events, transformation to acute leukemia, myelofibrosis and survival were evaluated. RESULTS: Sixty-six patients were evaluated. Thirtysix (54.5%) were females, with a median age at diagnosis of 61 years. At diagnosis, the median hemoglobin concentration was 18.8 mg/dl and the median platelet count was 593,000/mm3. Fifty-eight patients (88.0%) were treated with hydroxyurea with or without phlebotomy. During a median follow-up of 77 months, 22 patients (33.3%) had new thrombotic events, mainly of arterial type. The overall incidence of leukemia and myelofibrosis was 0.42% per patient-year and 1.06% per patient-year, respectively. Median overall survival was not reached and the seven-year survival rate was 77.8%. CONCLUSION: The PV patients described here had long survival and arterial thrombotic events were the most important and common complication among this population.